Understanding household vegetable gardening in Quezon city insights from household gardeners - CGIAR Initiative on Resilient Cities (CGIAR Initiative on Resilient Cities, 2024)
Under the Work Package 1 of the CGIAR Resilient Cities Initiative, the World Vegetable Center partnered with Ateneo de Manila University and the Quezon City government through the QC Food Security Task Force office to survey urban gardeners to understand their sources of planting material and analyze their demand for quality seedlings. The results of this study will be used to foster the development of entrepreneurial ventures around vegetable seedlings and related urban farming initiatives in selected communities.